2021 Tajogaite eruption records infiltration of crustal fluids within the upper mantle beneath La Palma, Canary Islands - Sandoval-Velasquez, A.; Casetta, F.; Ntaflos, T.; Aiuppa, A.; Coltorti, M.; Frezzotti, M. L.; Alonso, M.; Padrón, E.; Pankhurst, M.; Pérez, N. M.; Rizzo, A. L. (Frontiers in Earth Science, 2024)
The 2021 Tajogaite eruption at La Palma has represented a unique opportunity to investigate the characteristics of the mantle source feeding modern volcanism in the Canary Islands. With the aim of track the fingerprint of carbon in the local oceanic lithosphere-asthenosphere system, we report the isotopic composition of CO2 (δ 13 C values versus Vienna Pee Dee Belemnite) in olivine-and clinopyroxene-hosted fluid inclusions (FI) from the 2021 Tajogaite lavas and from lavas/ultramafic xenoliths (olivine-clinopyroxenites, clinopyroxenites, dunites and harzburgites) from the nearby 1677 San Antonio eruption cone/lavas, in an attempt to characterize the origin and evolution of carbon within the local mantle source. Our results indicate that the 2021 and 1677 lavas exhibit δ 13 C values ranging from -4.94‰ to -2.71‰ and CO2/ 3 He ratios from 3.37 to 6.14×10 9 . Ultramafic xenoliths fall in a comparable range of values despite showing higher CO2 concentrations. Our δ 13 C values fall within the range of carbon isotope results previously reported for the Dos Aguas cold spring located in the Taburiente Caldera (northern La Palma), suggesting an apparent carbon isotope homogeneity at the scale of the entire island. The (relatively narrow) δ 13 C vs. CO2/ 3 He ratio range of La Palma samples is interpreted to reflect either (i) variable extents of open-system degassing of a common mantle endmember having δ 13 C of 1.7‰, or (ii) mixing between depleted mantle-like carbon (-6‰<δ 13 C<-4‰) and crustal carbon (δ 13 C = 0‰) endmembers. Both models testify a crustal carbon component recycled in the local mantle. This component, also detected in mantle xenoliths from the neighboring island of El Hierro and the easternmost Lanzarote, indicates a regional characteristic of the mantle beneath the Canary Islands, interpreted as a result of infiltration of carbon-rich melts during past metasomatic events in the local mantle.